MMP1 drives tumor progression in large cell carcinoma of the lung through fibroblast senescence. (1st June 2021) - Gabasa, Marta; Radisky, Evette S.; Ikemori, Rafael; Bertolini, Giulia; Arshakyan, Marselina; Hockla, Alexandra; Duch, Paula; Rondinone, Ornella; Llorente, Alejandro; Maqueda, Maria; Davalos, Albert; Gavilán, Elena; et al.
Abstract: Large cell carcinoma (LCC) is a rare and aggressive lung cancer subtype with poor prognosis and no targeted therapies. Tumor-associated fibroblasts (TAFs) derived from LCC tumors exhibit premature senescence, and coculture of pulmonary fibroblasts with LCC cell lines selectively induces fibroblast senescence, which in turn drives LCC cell growth and invasion. Here we identify MMP1 as overexpressed specifically in LCC cell lines, and we show that expression of MMP1 by LCC cells is necessary for induction of fibroblast senescence and consequent tumor promotion in both cell culture and mouse models. We also show that MMP1, in combination with TGF-β1, is sufficient to induce fibroblast senescence and consequent LCC promotion. Furthermore, we implicate PAR-1 and oxidative stress in MMP1/TGF-β1-induced TAF senescence. Our results establish an entirely new role for MMP1 in cancer, and support a novel therapeutic strategy in LCC based on targeting senescent TAFs. HIGHLIGHTSGabasa et al., MMP1 drives tumor progression in large cell carcinoma of the lung through fibroblast senescence : Large cell carcinoma (LCC) of the lung is a rare and aggressive lung cancer subtype. Tumor-associated fibroblasts from LCC patients exhibit premature senescence. MMP1 and TGFB1 are overexpressed in LCC cells. MMP1 in LCC cells is necessary for induction of fibroblast senescence and consequent tumor promotion. MMP1 and TGF-β1 are sufficient to induce fibroblast senescence and enhance tumor promotion.